A web-based intervention is feasible for supporting weight loss and increased activity in rural women with arthritis - Patricia A. Hageman; Christine Eisenhauer; Joseph E. Mroz; Rebecca Johnson Beller (SAGE Publishing, 2021)
Rural women have well documented health disparities, with higher prevalence of obesity and chronic conditions, including arthritis. Change in weight and actigraph-recorded data were examined in a subset of 63 of 82 women with physician-diagnosed arthritis who completed a 30-month web-based clinical trial. Repeated measures analyses showed women lost weight from baseline to six months, slowly regained at 18 and 30 months, ending with a lower weight than baseline F(1,62)=40.89, p < .001, η2p =.40. Of 53 women with complete data, activity increased at six months, decreased at 18 months, and increased at 30 months F(1,52)=4.14, p =.04, η2p=.07. Women showed improved change in weight and activity from baseline at six, 18 and 30 months. This study adds support that web-based programs may promote weight loss and activity in a hard-to-reach, underserved population of midlife and older rural women with arthritis.